The modern slavery agenda : politics, policy and practice in the UK - Craig, Gary, 1944-; Balch, Alex; Lewis, Hannah, 1976-; Waite, Louise, 1975- (Policy Press, 2019)
"Modern slavery, in the form of labour exploitation, domestic servitude, sexual trafficking, child labour and cannabis farming, is still growing in the UK and industrialised countries, despite the introduction of laws to try to stem it. This hugely topical book, by a team of high-profile activists and expert writers, is the first critically to assess the legislation, using evidence from across the field, and to offer strategies for improvement in policy and practice. It argues that, contrary to its claims to be 'world-leading', the Modern Slavery Act is inconsistent, inadequate and punitive; and that the UK government, through its labour market and immigration policies, is actually creating the conditions for slavery to be promoted."--